The public choice of public stadium financing: Evidence from San Diego referenda - Candon Johnson; Joshua C. Hall (Economies, 2019)
Local politicians and team owners frequently argue that the public financing of stadiums is important for local economic development. The sports economics literature, however, has largely found that new professional sport facilities do not generate any new net economic activity. We provide context to this literature by exploring the public choice in the public financing of stadiums. In 2016, San Diego had two ballot measures related to the San Diego Chargers. Measure C would allow officials to raise hotel taxes to pay for a new downtown stadium for the Chargers. Measure D would also raise hotel taxes, but explicitly prevented any money being spent on the Chargers. Both measures failed to receive 50% of the votes cast. We find that zip codes with a higher voter turnout were more likely to vote against both measures, highlighting the importance of the timing of referenda in limiting the ability of clearly defined groups, such as Chargers fans, to have a large influence on the voting outcome. Meanwhile, areas with more Trump voters were more likely to support higher taxes for the purpose of building the Chargers a new stadium.
Keywords: D72; Z20; 330; voting behavior; National Football League; Donald Trump